Забезпечення права на страйк у міжнародно-правових актах, ратифікованих Україною - Волохов, О.С. (Альманах права, 2012)
Досліджуються питання, пов’язані з правовою регламентацією страйків у актах міжнародного регулювання праці, прийнятих Україною. Аналізується відповідність вітчизняного трудового законодавства їх положенням. Исследуются вопросы, связанные с правовой регламентацией забастовок в актах международного регулирования труда. Анализируется соответствие украинского трудового законодательства их положениям. The right to strike is one of the oldest ways of workers rights protection. Having a great historical background of foundation and development, this right is mentioned in special laws and constitutions of different countries all over the world, it is regulated by international legal acts and general principles of law. The role of strike in present
Ukrainian conditions is growing, as taking into the account the problems of timely salary payment, low social guarantees etc. At the same time, the realization of right to strike is quite complicated task in Ukraine because of different law restraints, gaps in national law and lots long termed formal procedures. Also most of these problems
are unsolved by the current version of draft of the Labour code of Ukraine, which is at the second reading now. For example, there is a great need of new terminology, simplification of formal procedures and terms in this draft code. To solve these and other problems the country should use the provisions of international legal acts when applying or upgrading its national labour law. At the same time, the way of realization of right to strike varies in different countries as it is mostly regulated by international regional legal acts. There are only few universal international legal
acts in this sphere. It is resulted by employer’s unions’ position of restraining strikes and the attitude of International labour organization (ILO) to the right of strike: the organization is mostly concentrated on peaceful solution of labour
conflicts, which is just the opposite to the strike. At the universal level the right to strike is provided by International Covenant on Economic, Social and Cultural Right 1966 which was adopted by Ukraine in 1973; and it is mentioned in Convention No 105 and Recommendation No 92. Also it is regulated by the principles of freedom of association
committee of ILO, which arise from the interpretation of ILO Conventions No87 and No 98 and are analysed for their accordance to Ukrainian labour legislation. As for regional legal acts, the right to strike is provided by the European Social Charter 1996, Community Charter of the Fundamental Social Rights of Workers 1989, Charter of
Fundamentional Rights of European Union 2000. It is pointed out in the article that the subjects of right to strike are wider in article 6 of European Social Charter than it is in Ukrainian law. Moreover this provision of Charter allows the use of lock-out by employers in reply of workers strikes. In conclusion, it is realized that Ukrainian labour law has some mismatches with the provisions of international legal acts in sphere of providing of right to strike ratified by Ukraine. So the recommendation is to follow these
provisions during the next reformation of Ukrainian labour law, keeping in mind that providing of right to strike in some measures is needed to lower the social tension and to direct the discontent of workers to legitimated ways.